The Art of Ikat Weaning, Women, and the Transformation of Changes in Community's Socio-Cultural Life Sikka Maumere Flores NTT (Historical, Social, and Cultural Studies) - Dentis, Yosef (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research discusses the art of Ikat weaving, women, the meaning, and context of changes in the social cultural life of the people of Sikka Maumere Flores, NTT. The study uses qualitative descriptive methods in order to answer all the main problems in research using interview, observation, and documentation techniques. The main problem is the lack of actualization of growth and changes in Ikat Weaving Arts activities and contributions to society. The aim of the research is to find positive solutions for historical, socio-economic, and cultural change in Sikka Maumere. Sikka women are used as symbols who have a sense of artistry and are always articulate in weaving activities, showing a partner system that conveys the truth of the Flores tribe as an integral part of the Indonesian nation, directed at partners and co-workers with local cultural identity. The results of the research are significant: Women have had a positive impact on changes in Sikka Maumere Women's and Weaving Arts activities as an effort to preserve and develop a culture that adopts a global mindset but still acts to maintain local wisdom.